Continental scale variation in 17O-excess of meteoric waters in the United States. (1st September 2015) - Li, Shuning; Levin, Naomi E.; Chesson, Lesley A.
Abstract: High-precision triple oxygen isotope analysis of waters is an emerging tool in hydrological and paleoclimate research. The existing research on 17 O-excess in waters includes surveys of meteoric waters and region-specific studies of high-latitude snow and tropical storms. However, a better understanding of the variation in 17 O-excess of waters across large geographic regions is needed to expand the utility of triple oxygen isotope measurements. Here we present 17 O-excess data from tap waters across the continental U.S., which we used as a proxy for precipitation. The 17 O-excess values of tap waters ranged from −6 to +43 per meg and averaged 17 ± 11 per meg which is lower than the average 17 O-excess reported for global meteoric waters, but overlaps with reported 17 O-excess values of rainfall from the tropics. We observed relatively high 17 O-excess values (>25 per meg) of tap waters in the northwestern U.S. and some of the lowest 17 O-excess values (<5 per meg) in the states bordering the Gulf of Mexico. The latitudinal variation of 17 O-excess among tap waters likely reflects the different controls on 17 O-excess in precipitation. For example, re-evaporation of precipitation and convective processes influence the isotopic composition of tap waters from the southern portions of the U.S., resulting in relatively low 17 O-excess values. In contrast, these effects are reduced in tap waters from the northern portions of the U.S. where snow and cold-season rainfall are primarily responsible for the majority of annual precipitation. Exceptions to the latitudinal trend are prevalent in the central portions of the U.S., where mixing and convection are likely responsible for 17 O-excess values that are lower than would be expected at their latitudes. The results of this study provide both a first look at the variation of 17 O-excess in meteoric waters on a continental scale and a predictive map for 17 O-excess of meteoric waters in the U.S.